Today's relevancy of the migration determinants theory - Baba, Baayah; Mc Gregor, Peter; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
There are many theories of migration. The human capital, search and the gravity models are among the most widely referred to by researchers. The influence of house prices, job vacancies, wage differentials on the migration decisions have widely been noted and have the expected signs. However, in a study done using the Scottish data the house price variables seem to give an opposite sign that contradicts previous findings. Perhaps comfortable house and available entertainment facilities matters and not just the house price that affects the decision to migrate. Future studies should include the entertainment facilities as one of the determining factor of migration.